Construction and application of hybrid covalent adaptive network with non-conjugated fluorescence, self-healing and Fe3+ ion sensing - Wencan Luo; Hui Yu; Zhenzhen Liu; Rongxian Ou; Chuigen Guo; Tao liu; Jinwen Zhang (Journal of Materials Research and Technology, 2022)
Herein, a non-conventional fluorescent polymer (NCFP) was established by coupling in-situ Schiff base reaction with epoxy ring-open polymerization, which were constructed by hyperbranched polyamidoamine (HPAMAM) and bio-based vanillin epoxy monomer with an aldehyde group (MB). The resulting hybrid covalent adaptive networks (HP/MB) could emit strong intrinsic fluorescence due to the non-conjugated fluorescence derived from HPAMAM, and the fluorescence intensity shows a good linear correlation with the crosslink density. Meanwhile, owing to the epoxy-Schiff base hybrid covalent adaptive network, HP/MB exhibit excellent mechanical properties and self-healing that can be monitored in real time by fluorescence imaging. As a representative, HP/MB-3 exhibited a tensile strength up to 76.4 MPa, and achieved 100% repair of the crack within 4 min at 140 °C under 1.5 MPa pressure. Especially, HP/MB-3 also showed strong fluorescence quenching by Fe3+ ion. Based on the above unique properties, the application potential of HP/MB in responsive metal coating were further explored, and the coated sample could exhibit different degree of fluorescence quenching effect at different corrosion stages. Therefore, the NCFP-based HP/MB possesses great application potential in the areas of fluorescent sensors, anti-counterfeiting labels, self-detecting anticorrosive coatings and engineering damage assessment.